URGENSI PERJANJIAN DALAM LALU LINTAS HUBUNGAN HUKUM PERDATA - Rosdalina Bukido (IAIN Manado, 2008)
An agreement is an event of where a promising to another of where two the means is each promise to execute a thing. Execution of this agreement become purpose of people whe make an agreement, because of exactly with execution of the agreement, the party making it will be able to fulfill it’s the king be able to fulfill it’s requirement. Agreement is deed of real important law done by the parties in civil contractual terms before executing law deed. This thing is important is done for shake of creation of peacefulness and the parties justice. Agreement loads rights and obligations any kind of that must be done by the parties, so that if it is then day one them is default hance young referred to contents of agreement. Agreement gives protection of law the parties.